2007
DOI: 10.1039/b700389g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of mesoporous carbon for fuel cell applications

Abstract: The synthesis and application aspects of ordered mesoporous carbon (OMC) as a novel material for fuel cell catalysts are reviewed in this paper. The synthesis and structural characterization of OMC is outlined and the recent advances in the synthesis of OMC relevant to fuel cell technologies is presented. Recent examples of the application of OMC as a support for fuel cell catalysts are summarized and practical approaches for the application of OMC for the fuel cell systems are discussed. Future perspectives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
224
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 347 publications
(225 citation statements)
references
References 83 publications
(115 reference statements)
0
224
0
1
Order By: Relevance
“…The total loading of Pt was controlled as high as 60 wt%, because an electrocatalyst for DMFC application requires very high metal loading (Chang et al, 2007). The TEM image of Pt/OMC ( Fig.…”
Section: Characteristics Of Omc Support and Pt/omc Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…The total loading of Pt was controlled as high as 60 wt%, because an electrocatalyst for DMFC application requires very high metal loading (Chang et al, 2007). The TEM image of Pt/OMC ( Fig.…”
Section: Characteristics Of Omc Support and Pt/omc Catalystmentioning
confidence: 99%
“…The Pt/OMC catalysts have been developed in our lab over several years for the DMFC, which is based on the novel OMC supports having very high surface area and ordered array of mesopores inside the particles (Chang et al, 2007, He et al, 2010, Joo et al, 2009., Lee et al, 2009, Pak et al, 2009.…”
Section: High Performance Mea Using New Supported Catalystmentioning
confidence: 99%
“…In an attempt to improve catalyst utilisation, non-conventional carbon and non-carbonaceous catalyst supports have been recently developed, e.g. ordered mesoporous carbons [55], carbon nanotubes [56], graphene and graphene oxides [57] and conducting polymers [58]. Notably, ordered mesoporous carbons feature highly controllable structure, size and pore size and some of the recent relevant experimental studies have shown promising results [59,60].…”
Section: Introductionmentioning
confidence: 99%
“…The application of mesoporous carbon (MC) as a catalyst support material has been studied extensively due to its favorable properties for PEM fuel cell electrodes [1][2][3][4][5][6][7][8][9][10]. The high surface area allows for a fine dispersion of Pt nanoparticles, thus resulting in a large active catalyst surface.…”
Section: Introductionmentioning
confidence: 99%